Onset and temporal sequencing of lifetime anxiety, mood and substance use disorders in the general population. (February 2015) - Slade, T.; McEvoy, P. M.; Chapman, C.; Grove, R.; Teesson, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Aims. To date, very few studies have examined the bi-directional associations between mood disorders (MDs), anxiety disorders (ADs) and substance use disorders (SUDs), simultaneously. The aims of the current study were to determine the rates and patterns of comorbidity of the common MDs, ADs and SUDs and describe the onset and temporal sequencing of these classes of disorder, by sex. Methods. Data came from the 2007 Australian National Survey of Mental Health and Wellbeing, a nationally representative household survey with 8841 (60% response rate) community residents aged 16–85. Results. Pre-existing mental disorders increase the risk of subsequent mental disorders in males and females regardless of the class of disorder. Pre-existing SUDs increase the risk of subsequent MDs and ADs differentially for males and females. Pre-existing MDs increase the risk of subsequent ADs differentially for males and females. Conclusions. Comorbidity remains a significant public health issue and current findings point to the potential need for sex-specific prevention and treatment responses.